Chinese Women’s Family Status: Analysis of Chinese Decennial Surveys, 1990-2010 - Lu, Jiehua; Wang, Xiaofei (Kvinder, Køn & Forskning, 2015)
The experiences and status of Chinese women have significantly changed over the last two to three decades, along with China’s modernization. In this article we investigate the domestic division of labor between the two sexes at the present-day in the context of gender equality. Based on data from three Surveys on Chinese Women’s Social Status taken in 1990, 2000 and 2010, the article focuses on important dimensions of women’s family status, such as general changes in domestic decision-making and the time women spend in domestic labor, including rural-urban differences. The article points to “equal rights for both husband and wife” (Fu Qi Ping Quan, 夫妻平权) as being the major pattern in domestic decision-making, yet men have still more rights than women. Also, women are still the main force in domestic labor, although the difference between the times spent in domestic labor by women and men respectively has gradually narrowed. There also seems to be a greater correlation between education and women’s status in rural areas than in urban areas.